2015
DOI: 10.1097/md.0000000000001849
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcomes of Acute Respiratory Distress Syndrome

Abstract: Most epidemiological studies of acute respiratory distress syndrome (ARDS) have been conducted in western countries, and studies in Asia are limited. The aim of our study was to evaluate the incidence, in-hospital mortality, and 1-year mortality of ARDS in Taiwan.We conducted a nationwide inpatient cohort study based on the Taiwan National Health Insurance Research Database between 1997 and 2011. A total of 40,876 ARDS patients (68% male; mean age 66 years) were identified by International Classification of Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 50 publications
1
32
0
Order By: Relevance
“…In the last decade, numerous approaches have been proposed to treat ARDS, such as improvements in fluid administration, non-invasive mechanical ventilation strategies and ventilator management ( 6 9 ). Although in-hospital and 1-year mortality rates have decreased by a certain degree in recent years, ARDS still leads to a heavy social burden and high health-care cost ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, numerous approaches have been proposed to treat ARDS, such as improvements in fluid administration, non-invasive mechanical ventilation strategies and ventilator management ( 6 9 ). Although in-hospital and 1-year mortality rates have decreased by a certain degree in recent years, ARDS still leads to a heavy social burden and high health-care cost ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, European estimates are more conservative, ranging between 4.2 and 13.5/100,000 per year (Webster et al, 1988;Luhr et al, 1999). However, epidemiological studies conducted in Asia are limited (Singh et al, 2014;Chen et al, 2015). A recent systemic review suggests that the mortality rate for ARDS is between 36% and 44% (Phua et al, 2009).…”
mentioning
confidence: 99%
“…27 A study of hospital discharges in Taiwan also demonstrated an increase in ARDS population incidence from 3 to 19 cases per 100,000 persons per year from 1997 to 2011. 43 In contrast, a third study from 2001 to 2008 in Olmsted County, Minnesota, demonstrated a decrease in ARDS incidence from 82 to 39 cases per 100,000 persons per year. While these studies are informative for their respective populations and to the extent that the Olmsted study generated hypotheses for preventing ARDS through hospital-wide health care practices, the geographic variation of the incidence of ARDS advises toward caution in extrapolating these trends to other contexts.…”
Section: Temporal Trends In Ards Incidencementioning
confidence: 94%